Diagnostic value of CEACAM6 and HE4 in pleural fluid for malignant pleural effusion - Jie Li; Liyuan Lin; Shengrui Yang; Yuan Mu; Lixia Zhang; Haoyu Ruan; Jian Xu (Annals of Medicine)
Objective This study aimed to assess the diagnostic performance of carcinoembryonic antigen-related adhesion molecule 6 (CEACAM6) and human epididymis protein 4 (HE4) in pleural fluid for the detection of malignant pleural effusion (MPE).Materials and methods In this prospective study, pleural levels of CEACAM6 and HE4 were measured in two independent cohorts. The test cohort included 182 patients with exudative pleural effusions (123 malignant and 59 benign), and the validation cohort comprised 117 patients with exudative pleural effusions (65 malignant and 52 benign). Receiver operating characteristic (ROC) curves were used to assess the diagnostic performance of CEACAM6 and HE4 for MPE.Results Both CEACAM6 and HE4 levels were significantly elevated in MPE compared to benign pleural effusion (BPE) in both cohorts (p < .001). In the test cohort, CEACAM6 and HE4 demonstrated areas under the curve (AUC) values of 0.862 and 0.826, respectively. The combination of CEACAM6 and HE4 yielded a higher AUC of 0.938 compared to either marker alone. In the validation cohort, both CEACAM6 (AUC = 0.811) and HE4 (AUC = 0.721), along with their combination (AUC = 0.834), exhibited strong diagnostic performance for MPE. Notably, in cytology-negative cases, the combination of CEACAM6 and HE4 also demonstrated a favourable diagnostic efficacy, with an AUC of 0.800. The addition of CEA to the CEACAM6/HE4 combination further improved the AUC to 0.819 (p = .04).Conclusions Pleural CEACAM6 and HE4 are promising biomarkers for distinguishing MPE from BPE. Their combination improves diagnostic accuracy, offering a valuable tool for MPE diagnosis, especially in challenging cases with cytology-negative pleural effusion.